A critical overview and examination of global financial architecture proposals and their relevance to small economies - Pérez, Esteban ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2004)
Provides a critical overview and examination of global financial architecture proposals and highlights their relevance to smaller economies.